2014
DOI: 10.1111/1346-8138.12483
|View full text |Cite
|
Sign up to set email alerts
|

Histological studies of facial acne and atrophic acne scars treated with a bipolar fractional radiofrequency system

Abstract: Various fractional radiofrequency (FRF) treatments have demonstrated significant beneficial effects and minor side-effects on atrophic acne scars and acne vulgaris by creating micro-thermal injuries in the skins. However, histological studies to identify the precise mechanism responsible for the success of bipolar FRF treatments are lacking. In this study, six human subjects with these diseases were histologically analyzed after treatment with a bipolar FRF system (eMatrix; Syneron, Yokneam, Israel) and the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
1
10
0
1
Order By: Relevance
“…discovered increases in the levels of procollagen types I and III, as well as elastin. In addition, in our previous study of atrophic acne scars we observed the thermal denaturation of peri‐hair follicle collagen, hair follicles and sebaceous glands . These results indicate that bipolar FRF treatment can lead to collagen fiber remodeling in the deep dermis and also affects adnexal structures.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…discovered increases in the levels of procollagen types I and III, as well as elastin. In addition, in our previous study of atrophic acne scars we observed the thermal denaturation of peri‐hair follicle collagen, hair follicles and sebaceous glands . These results indicate that bipolar FRF treatment can lead to collagen fiber remodeling in the deep dermis and also affects adnexal structures.…”
Section: Discussionsupporting
confidence: 51%
“…In addition, in our previous study of atrophic acne scars we observed the thermal denaturation of peri-hair follicle collagen, hair follicles and sebaceous glands. 21 These results indicate that bipolar FRF treatment can lead to collagen fiber remodeling in the deep dermis and also affects adnexal structures. Acne vulgaris is a disorder that involves increased sebum production, keratinocyte proliferation within the follicular epithelium and follicular colonization by Propionibacterium acnes, and these symptoms are the main targets of treatment.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…A similar effect was found in our study; as the number of treatments increased, both radiofrequency instruments were able to improve active acne. Several studies have explored the mechanism of radiofrequency treatment for the treatment of active acne, which may include heat generated by radiofrequency inducing thermal denaturation of the peri‐hair follicle collagen, hair follicle, and sebaceous gland and killing of C acnes , the pathogenic factor in the development of acne vulgaris.…”
Section: Discussionmentioning
confidence: 99%